Inventory Management Concepts and Implementations: A Systematic Review - Munyaka, J.B.; Yadavalli, V.S.S. (South African Journal of Industrial Engineering, 2022)
Inventory is a central management function. It is a cornerstone of supply chain management and logistics in the material management system. Depending on the organisational objectives, inventories in warehouses may be needed to fulfil customer or humanitarian demands. Controlling inventory is critical to operational success and organisational performance. This research reviews inventory management concepts and implementations in the face of increasingly demanding human need. Demand is a critical variable in the inventory control system, and its characteristics affect inventory treatment. Important demand characteristics include its level of certainty, which could be deterministic (i.e., known with certainty) or stochastic/Bayesian (i.e., known but uncertain), and its structural dependency (i.e., independent or dependent). This review considers the deterministic independent and dependent natures of demand and their respective impact on inventory management in operations.